Nanoporous Atomically Thin Graphene Membranes for Desalting and Dialysis Applications. Issue 33 (28th June 2017) - Kidambi, Piran R.; Jang, Doojoon; Idrobo, Juan‐Carlos; Boutilier, Michael S. H.; Wang, Luda; Kong, Jing; Karnik, Rohit
Abstract : Dialysis is a ubiquitous separation process in biochemical processing and biological research. State‐of‐the‐art dialysis membranes comprise a relatively thick polymer layer with tortuous pores, and suffer from low rates of diffusion leading to extremely long process times (often several days) and poor selectivity, especially in the 0–1000 Da molecular weight cut‐off range. Here, the fabrication of large‐area (cm 2 ) nanoporous atomically thin membranes (NATMs) is reported, by transferring graphene synthesized using scalable chemical vapor deposition (CVD) to polycarbonate track‐etched supports. After sealing defects introduced during transfer/handling by interfacial polymerization, a facile oxygen‐plasma etch is used to create size‐selective pores (≤1 nm) in the CVD graphene. Size‐selective separation and desalting of small model molecules (≈200–1355 Da) and proteins (≈14 000 Da) are demonstrated, with ≈1–2 orders of magnitude increase in permeance compared to state‐of‐the‐art commercial membranes. Rapid diffusion and size‐selectivity in NATMs offers transformative opportunities in purification of drugs, removal of residual reactants, biochemical analytics, medical diagnostics, therapeutics, and nano‐bio separations. Abstract : The synthesis of novel nanoporous atomically thin graphene membranes for desalting and dialysis applications is reported. A facile oxygen‐plasma etch on defect‐sealed graphene enables size‐selective separation and desalting of small model molecules (≈200–1355 Da) and proteins (≈14 000 Da), with ≈1–2 orders of magnitude increase in permeance compared to state‐of‐the‐art commercial membranes.